Vsevolod Meyerhold - Pitches, Jonathan, 1968- (Routledge performance practitioners., 2003)
This is the first book to combine biographical introduction to Meyerhold's life, his theoretical writings, analysis of 'Revisor, or The Government Inspector' and the 'biomechanical' exercises he developed for actor training.